RELEITURA DO PRINCÍPIO DO LIVRE CONVENCIMENTO MOTIVADO DO JUIZ EM MATÉRIA DE FORNECIMENTO DE MEDICAMENTO NÃO INCORPORADO AO SUS (Reflection and Critique Law Magazine, 2025)
The present study analyzes, from the perspective of the Judiciary and the role of Public Advocacy, legal claims related to the provision of medications not incorporated into the Universal Health System of Brazil, with emphasis on the impact of "reasoned free conviction" on judicial decisions and the need for judicial self-restraint in technical matters concerning Public Health. The discussion highlights the relevance of detailed judicial reasoning and the consideration of technical evidence, such as the analysis of recommendations from Conitec and technical notes from NATJUS, in light of the recently issued binding theses No. 6 and No. 1,234 of general repercussion. The study concludes that the judge's "reasoned free conviction" should be maintained but subject to a necessary reinterpretation to ensure due consideration of Public Health Policy and the technical bodies involved therein, without compromising judicial autonomy.